STARCH COMPOSITION RELATED TO PHYSICAL TRAITS IN MAIZE KERNEL - Milašinović, Marija (Journal on Processing and Energy in Agriculture, 2021)
The focus of this study is on the physical quality traits and starch composition of various maize kernel genotypes grown in Serbia. Furthermore, the aim was to determine the relationship among these quality traits. Results obtained from the Stenvert hardness test showed great variability among the maize samples. The portion of the hard endosperm fraction (HE) ranged from 53.29% to 76.28%. Test weight (TWt) and 1000-kernel weight (KWt) of 10 different ZP maize genotypes ranged from 782.69 to 907.39 kgm-3 and from 128.40 to 376.50 g, respectively. The specialty maize genotypes had the highest content of amylose (27.8% and 28.9%). Yellow dent genotype, ZP 606, had the lowest amylose content in the kernel (22.3%). The results suggested that the composition of starch granule differed depending on the hardness of the endosperm. The amylose content was highly correlated with the physical traits such as TWt, KWt, density and HE.
Keywords: maize genotypes, kernel, starch composition, physical traits